Electrophoretic Codeposition of La0.6Sr0.4Co 0.8Fe0.2O3-δ and carbon nanotubes for developing composite cathodes for intermediate temperature solid oxide fuel cells - Santillán, María José (2010)
Carbon nanotubes (CNTs)/La0.6Sr0.4Co 0.8Fe0.2O3-δ (LSCF) composite films have been fabricated by electrophoretic codeposition on Ce0.9Gd 0.1O1.95 (CGO) substrates. CNTs are used as a sacrificial phase to produce ordered porous LSCF cathodes for intermediate temperature solid oxide fuel cells. The synthesis of LSCF powder by a modified sol-gel route is presented. The possible mechanism of formation of CNT/LSCF composite nanoparticles in suspension is discussed. Moreover the optimal suspension composition and the conditions for achieving successful electrophoretic deposition (EPD) of CNTs/LSCF composite nanoparticles were evaluated. Experimental results showed that the CNTs were homogeneously distributed and mixed with LSCF nanoparticles forming a mesh-like structure, which resulted in a highly porous LSCF film when the CNTs were burned out during heat treatment in air at 800°C for 2 h. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD) techniques were employed to characterize the microstructure of the precursors and of the composite films.